The comparison of the hedonic, repeat sales, and hybrid models: Evidence from the Chinese paintings market - Fang Wang; Xu Zheng (Cogent Economics & Finance, 2018)
With the objective of evaluating the accuracy of price index models, we adopt a series of techniques to compares the performances of the hedonic, repeat sales, and hybrid models based on the data from the Chinese most representative painter, Qi Baishi during the period from 2000 to 2016. When applying the mean squared error (MSE) technique, the repeat sales model outperforms alternative models. However, according to the correlations and width confidence intervals, the hybrid model provides the most reliable estimates of price indices. The study also shows that the repeat sales model obtains relatively a lower total return estimate as well as a higher volatility than other two models. Our findings have important implications in identifying the precision of index models and provide supplements to art investment studies..
Keywords: C52; Z1; 330; Chinese paintings market; hedonic model; repeat sales model; hybrid model; art investment